Occurrence of phosphenolpyruvate carboxylase in the extremely thermophilic bacterium Thermus aquaticus. - Bridger, G P (1976)
In the extreme thermophile Thermus aquaticus, phosphoenolpyruvate carboxylase catalyzes carbon dioxide fixation on the C3 metabolite phosphoenolpyruvate, producing oxaloacetate. In a moderately thermophilic Bacillus species this function is fulfilled by pyruvate carboyxlase. Like several of its mesophilic counterparts, the Thermus enzyme exhibits a requirement for acetyl coenzyme A.